Design, Synthesis and Kinetic Study of Coumarin-Based Mutual Prodrug of 5-Fluorouracil and Dichloroacetic acid - F. Mustafa, Yasser; A. Al-Omari, Nohad (Iraqi Journal of Pharmaceutical Sciences, 2017)
On the basis of known coumarin-based prodrug system, a novel coumarin-based mutual prodrug of 5-fluorouracil and dichloroacetic acid was designed, synthesized and evaluated as a promising oral chemotherapeutic agent basing on in vitro stability study in HCl buffer (pH 1.2) and in phosphate buffer (pH 7.4), as well as in vitro release study in human serum. The chemical structure of prodrug was confirmed by analyzing its FTIR, 1H NMR, 13C NMR and MS-ESI spectra. The results of in vitro kinetic study indicated that the prodrug was significantly stable in HCl and in phosphate buffers, and was hydrolyzed in human serum followed pseudo first order kinetics.Keywords: Coumarin-based prodrug, 5-fluorouracil, Dichloroacetate, kinetics.